Personal Branding Guru PAI sebagai Cermin Reputasi Lembaga Pendidikan Islam - Aryogo Adi Guna; Supratman Zakir (Universitas 45 Surabaya, 2025)
This study examines the urgency of personal branding among teachers, particularly Islamic Religious Education (IRE) teachers, as a strategic element in strengthening the image and reputation of Islamic educational institutions amid increasingly competitive educational environments. Social changes, advancements in information technology, and rising public expectations regarding educational quality require teachers to function not only as educators in the classroom but also as representatives of institutional values, character, and identity. In this context, teachers’ personal branding becomes an important factor contributing to public trust and institutional attractiveness. This article employs a library research method using a descriptive-analytical approach by reviewing various literature sources, including books, scholarly journals, and other relevant publications. The analysis focuses on the concept of personal branding, teacher professionalism, and their relationship to the image of Islamic educational institutions. The findings indicate that the personal branding of IRE teachers, when grounded in professionalism, moral integrity, pedagogical competence, and personal authenticity, plays a significant role in enhancing institutional credibility in the eyes of the public. Teachers who consistently embody Islamic values in their attitudes, personal conduct, and professional practices are more likely to build trust, loyalty, and a positive institutional image. Therefore, strengthening the personal branding of IRE teachers not only contributes to individual professional development but also serves as an important strategy for improving the reputation, competitiveness, and sustainability of Islamic educational institutions in the modern era.